Sun Exposure across the Life Course Significantly Modulates Early Multiple Sclerosis Clinical Course - Simpson, Steve; van der Mei, Ingrid; Lucas, Robyn M.; Ponsonby, Anne-Louise; Broadley, Simon; Blizzard, Leigh; , Ausimmune/AusLong Investigators Group; Taylor, Bruce; Lucas, Robyn M.; Dear, Keith; Ponsonby, Anne-Louise; Dwyer, Terry; et al. (Frontiers in Neurology, 2018)
Background: Low vitamin D and/or sun exposure have been associated with increased risk of multiple sclerosis (MS) onset. However, few studies have prospectively examined associations between these factors and clinical course. Objectives: Evaluate the association of sun exposure parameters & vitamin D levels with conversion to MS and relapse risk in a prospectively monitored cohort of 145 participants after a first demyelinating event (FDE) followed up to 5-year review (AusLong Study). Methods: Sun exposure prior to and after onset measured by annual questionnaire; ultraviolet radiation (UVR) “load” estimated by location of residence over the life course and ambient UVR levels. Serum 25-hydroxyvitamin D (25(OH)D) concentrations measured at baseline, 2/3-year, & 5-year review. MS conversion and relapse assessed by neurologist review and medical record review. Results: Over two-thirds (69%) of those followed to 5-year review (100/145) converted to MS, with a total of 265 relapses. Higher pre-MS onset sun exposure was associated with reduced risk of MS conversion, with internal consistency between measures and dose-response relationships. Analogous associations were also seen with risk of relapse, albeit less strong. No consistent associations were observed between post-onset sun exposure and clinical course, however. Notably, those who increased their sun exposure during follow-up had significantly reduced hazards of MS conversion and relapse. Serum 25(OH)D levels and vitamin D supplementation were not associated with conversion to MS or relapse hazard. Conclusion: We found that pre-onset sun exposure was protective against subsequent conversion to MS and relapses. While consistent associations between post-onset sun exposure or serum 25(OH)D level and clinical course were not evident, possibly masked by behaviour change, those participants who markedly increased their sun exposure demonstrated a reduced MS conversion and relapse hazard, suggesting beneficial effects of sun exposure on clinical course.